(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The study was conducted to evaluate the effects of creep feeding on productive and reproductive performance of BLRI improved Non-descript Deshi (ND) chicken and their chick’s growth up to 8th week of age under semi-scavenging conditions at three different locations of Bangladesh. Two groups of farmers were selected from each location having the BLRI improved ND birds where one group used creep feeder and followed improved management practices, called creep feeding (CF) group. Another group of farmers rear ND chicken traditionally without using creep feeder, termed as non-creep feeding group (NCF) or control group. In CF trial, feeding groups had significant effects on hen weight loss during incubation, resume of laying, clutch size and clutch length (p<0.001). Hen weight loss was significantly lower in CF group (180g) than the NCF group (291g) during brooding of chicks. Hence, hens of CF group resume of laying about 2 weeks (13 days) earlier than the NCF group. Subsequently, the hens of CF group laid 29 eggs per clutch (37 days) in contrast to 23 eggs (38 days) by hens of NCF. However, the fertility and hatchability were insignificant (p>0.05) between the groups but higher in CF group than the NCF group as 82 and 76%, and 76 and 70%, respectively. Notably, the 8th week chick weight was 200g more in CF group than NCF group and the mortality was significantly (p<0.01) higher in NCF group (16%) than CF group (11%). However, feed intake of chicks didn’t differ significantly between the two feeding groups. In conclusion, CF found to be potentially contributed in better adaptation and efficient production performance of BLRI improved ND varieties under farmer’s condition and could be disseminated this management approach to farmers’ level for mass scale utilization. J Bangladesh Agril Univ 18(4): 1007–1012, 2020 https://doi.org/10.5455/JBAU.101532